Physicochemical composition of different parts of cassava (Manihot esculenta Crantz) plant - Idris, S.; S., Rosnah; M. Z. M., Nor; Mokhtar, M. N.; Abdul Gani, S. S. (Rynnye Lyan Resources, 2020)
Cassava (Manihot esculenta Crantz) is one of the main sources of carbohydrate and it is a useful plant in Malaysia. Its root is used to produce various foods such as cassava chips, while the other parts are potentially to produce feeds and other useful products. However, details observation in the proximate composition of each part of the cassava plant is important in utilizing it as an animal feed, especially for the ruminants. Hence, this research was conducted to evaluate the proximate composition of each part in the cassava plant and characterized its functional groups using Fourier-transform infrared spectroscopy (FTIR) and the thermal properties using thermogravimetric analyzer (TGA). The results obtained showed that the portions of fresh cassava plants namely flesh, stem, peel, discarded tuber and the leaf were recorded at 50.06%, 31.01%, 10.63%, 6.92% and 1.49% (w/w), respectively. Proximate analysis showed that the leaf has potential as animal feed as it contains significant high in crude protein (28.02±0.10%), crude fat (5.63± 0.12%) and the gross energy value of 4824.3 g/cal. Even though the leaf has a higher cyanide content (0.02 mg/kg) than other parts, it is still in acceptable range as an ingredient in animal feed. For animal feed that focuses on high protein and gross energy, the leaf has potential in feed ingredients. Meanwhile, cassava flesh also has potential as an animal feed since it has low crude fiber (2.11±0.03%) but high in carbohydrate (92.66±1.88%) and gross energy content (4223.9 cal/g). FTIR spectra showed that there were different functional groups present in the samples. From the TGA data, it showed that the major components in samples were cellulose which started to decompose rapidly at maximum degradation rate temperature of 315-400°C, especially for flesh and discarded tuber. Different parts of cassava plants are expected to help the agriculture industry in producing alternative animal feed at the same time minimizing the impact of waste generated in the environment.